2009
DOI: 10.1038/npp.2008.223
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Expression of the NMDA Receptor-Interacting Protein SynGAP Causes Behavioral Abnormalities that Model Symptoms of Schizophrenia

Abstract: Abnormal function of NMDA receptors is believed to be a contributing factor to the pathophysiology of schizophrenia. NMDAR subunits and postsynaptic-interacting proteins of these channels are abnormally expressed in some patients with this illness. In mice, reduced NMDAR expression leads to behaviors analogous to symptoms of schizophrenia, but reports of animals with mutations in core postsynaptic density proteins having similar a phenotype have yet to be reported. Here we show that reduced expression of the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
118
2
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(152 citation statements)
references
References 70 publications
(115 reference statements)
20
118
2
4
Order By: Relevance
“…With the use of a separately generated SynGAP Ï©/ÏȘ mouse, Muhia et al (2010) also demonstrated no difference in the withdrawal latency to thermal stimulation with altered SynGAP expression. Although Syn-GAP Ï©/ÏȘ mice, similar to the strain we used, exhibited an increase in spontaneous, seemly purposeless, open-field activity and an increased startle response, there was no evidence of gross sensory or motor dysfunction reported in these animals (Guo et al 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the use of a separately generated SynGAP Ï©/ÏȘ mouse, Muhia et al (2010) also demonstrated no difference in the withdrawal latency to thermal stimulation with altered SynGAP expression. Although Syn-GAP Ï©/ÏȘ mice, similar to the strain we used, exhibited an increase in spontaneous, seemly purposeless, open-field activity and an increased startle response, there was no evidence of gross sensory or motor dysfunction reported in these animals (Guo et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…This GAP plays an important role in models of synaptic plasticity (Kim et al 2003;Komiyama et al 2002;Rumbaugh et al 2006), apoptosis (Knuesel et al 2005), and schizophrenia (Guo et al 2009). SynGAP is associated with proteins in the postsynaptic density, including postsynaptic density-95 kDa and the N-methyl-D-aspartate (NMDA) receptor (Chen et al 1998;Kim et al 1998), and plays a crucial role in early development, since SynGAP knockout mice die within 1 wk of birth (Kim et al 1998).…”
mentioning
confidence: 99%
“…Le rĂŽle de SYNGAP pourrait ĂȘtre de restreindre dans le temps l'activation de RAS-ERK au cours de certaines phases de la plasticitĂ© synaptique. Les souris homozygotes pour un allĂšle nul de Syngap1 meurent Ă  la naissance tandis que les souris hĂ©tĂ©rozygotes survivent mais ont des perturbations de la mĂ©moire et des apprentissages [3,6].…”
Section: Processus Cognitifs Et Plasticité Synaptique : Cibles De La unclassified
“…En effet, le complexe Elongator, et plus particuliĂšrement sa sous-unitĂ© Elp3, possĂšde une activitĂ© histone acĂ©tyl-transfĂ©rase envers l'histone H3, rendant ainsi possible la progression de l'ARN polymĂ©rase II au niveau de la rĂ©gion transcrite de certains gĂšnes [4,5]. Des Ă©tudes rĂ©centes ont dĂ©montrĂ© qu'Elongator remplit aussi des fonctions dans le cytoplasme, comme la rĂ©gulation de l'exocytose et la modification de certains ARN de transfert [6,7].…”
Section: Nouvelleunclassified
See 1 more Smart Citation